Characterization of Silver Nanoparticles Prepared via Green Synthesis from Amomum Subulatum: Investigation of its Antioxidant, Antimicrobial and Catalytic Properties in Dye Degradation - Baghel, Sonam; Khurana, Monika; Gupta, Prachi (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The seeds extract of Amomum Subulatum commonly known as black cardamom is used for preparing Silver Nanoparticles (AgNps) via green route. The characterization of these nanoparticles was done by UV-visible, Fourier transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) techniques. The UV-vis spectra showed sharp absorption maximum at 432 nm that confirmed that AgNPs were synthesized successfully. The TEM measurements indicated that AgNps are mostly spherical with a few having hexagonal and trigonal shapes with size range of 13-21 nm. Dynamic Light Scattering (DLS) confirmed the stability of AgNps having negative zeta potential. XRD confirmed the mono-crystallinity of the prepared AgNps. A significant zone of inhibition is observed by these nanoparticles against gram positive and gram-negative bacteria. These nanoparticles exhibit a significant catalytic activity with respect of 4-nitrophenol (4-NP). The synthesized AgNps act as a catalyst and degraded the organic dyes, Methylene Blue (MB) and Methylene Orange (MO) by Sodium borohydride (NaBH4) as confirmed by UV-vis spectroscopy. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).